Pengaruh Perilaku Kepemimpinan, Motivasi Kerja, dan Pendidikan Terhadap Kinerja Pegawai - Muhammad Amir M; Labulan; Nicodemus Sere (Manajemen Pendidikan Program Doktor, 2021)
The purpose of this study was to determine the effect of the Leadership Behavior variable (X1), Work Motivation (X2) and Education Level (X3) which had a dominant effect on Employee Performance (Y) at the Mulawarman University Teacher Training and Education Faculty. The results of the study showed that based on the results of the research and analysis of the variables that affect the Leadership variable (X1) it has a significant effect on the Performance (Y) of the Teachers and Education Faculty employees of Mulawarman University. The partial test results show that the t test for Work Motivation variable (X2) on Performance (Y) with t count value of 1.668 is smaller than t table 0.260 or significance t = 1.668 smaller than  5%. This means that the Work Motivation variable (X2) has a significant influence on the Performance (Y) of the Teachers' School and Mulawarman University Education staff so that the hypothesis in this study is rejected. This indicates that work motivation is one of the ways used by a leader to exercise control. Based on the results of statistical analysis showing work motivation variables on the performance productivity of the Mulawarman University Teaching and Education Faculty employees, it was pointed out that motivation had a significant and significant effect on the performance productivity of the Mulawarman University Teaching and Education Faculty employees, this shows that the higher motivation of employees to work, the the high level of performance productivity of the Mulawarman University Teacher Training and Education Faculty employees. Based on the results of statistical analysis, the educational variables have a positive and significant effect on employee performance. The results of this study indicate that there is a positive relationship between education and the performance of the staff of the Teaching and Education Faculty of Mulawarman University so that the hypothesis in this study is universally universal.